Managerial calculations from the viewpoint of logic, analysis microeconomics and other theoretical disciplines - Hašková, Simona, 1973-; Jiroušek, Radim; Vysoká škola ekonomická v Praze. Fakulta managementu; Mrkvička, Tomáš (2015)
It is no secret that 'managerial' solutions are not, on average, nearly as reliable as 'technical' solutions. The focus of this work is to clarify the reasons why this is so, and to seek ways to increase the reliability of managerial solutions. The causes of this situation are both subjective (human factor failure), which can be influenced, and objective (complexity of the problem, the specifics of human behaviour, etc.) that can be only minimally influenced. Significant subjective causes at work were identified as: a. cognitive distortions at the mental level of thinking of the problem solvers; b. deficiencies in making inference and drawing conclusions; c. incorrect argumentation. There are two ways to reduce these causes: 1. cultivation of managerial thinking of the problem solvers; 2. the use of reserves in the implementation of approaches and tools of theoretical disciplines that already operate successfully elsewhere and are beneficial for managerial solutions. The first way deals with procedures for managerial solutions formulated in the language of the relevant discipline (the language of management), expressed by natural language and the chain of formulas (calculations) and visual (graphic) tools in the form of managerial decision trees, diagrams and charts with the rules of 'managerial logic'. This is generally defined as a set of approaches, tools, methods and skills needed for credible justification when solving managerial problems.
Specifically it deals with: - the 'case-based reasoning' approach, which aims at finding the best point of view on a given problem and analysing all considered aspects within its context step-by-step in detail; - translating the tools and methods of modern logic (especially its intuitionistic version) from the language of logic into the language of management taking into account the factual content of expressive means of the language of management including the ability of their effective application; - respecting the principles of rational and ethical argumentation within managerial solutions. The second way circumvents managerial solution procedures by recasting the managerial task to the task of a scientific discipline (logic, game theory, etc.) and derives the correct result therein. In this context we talk about the use of knowledge of theoretical disciplines in management. Both of these ways are demonstrated in the work in a number of illustrative examples and the annexed case studies addressing the specific tasks of managerial practice.
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2015
Vedoucí práce: Radim Jiroušek
Obsahuje bibliografii
Rok obhajoby 2015
Textový (vysokoškolská kvalifikační práce)
Keywords: rozhodování; argumentace; matematické modelování; management [obor disert. práce]; disertace; decision making; argumentation; mathematical modeling; dissertations